Augmented : Life in the Smart Lane. - King, Brett (Marshall Cavendish International, 2016)
The Internet and smartphone are just the latest in a 250-year- long cycle of disruption that has continuously changed the way we live, the way we work and the way we interact. The coming Augmented Age, however, promises a level of disruption, behavioural shifts and changes that are unparalleled. While consumers today are camping outside of an Apple store waiting to be one of the first to score a new Apple Watch or iPhone, the next generation of wearables will be able to predict if we're likely to have a heart attack and recommend a course of action. We watch news of Google's self-driving cars,